Pareto lÃ©vy in Islamic stock markets: a research agenda for Islamic finance - Chong Hui Ling, Felicia; Muhamad, Rusnah (International Journal of Engineering and Technology, 2019)
This research note suggests an alternative approach to study the characteristics of Islamic financial markets in ways allowing one to observe the actual characteristics of the market and to model its characteristics analytically while avoiding incorrect postulations especially during high market volatility. It unfolds the non-Gaussian truth when managing Islamic portfolios to pave ways for prudent portfolio approaches. We present this approach using mathematical illustrations and specific structures in physics to reinforce new orientation and strategy in Islamic equities management. Our observation suggests that future investigations should consider anomalous volatilities in modeling the financial markets for enhanced portfolio management.Â Â